Understanding the initial impact of early support and key working training through the voices of trainers, training participants, and families - Nascimento, Ana Teresa Brito (2021)
An exploratory study is reported of the delivery of the Early Support and Key Working (ES&KW) training program in England for multiagency professionals and parents. This qualitative study examined how ES&KW training principles and content relate to contemporary pillars in early childhood intervention; how this training is structured to meet the program’s principles and desired outcomes; and its impact on training participants’ competences to fulfill the key working functions in partnership with parents/carers and families they work with. The study involved, throughout its different phases, 42 participants, comprising trainers, training participants, mostly working with small children (aged 0–8 years), and families. On the basis of document analysis, training observations, focus groups, reflective practice, and semistructured interviews, results show that overwhelmingly participants found ES&KW training very significant to their work with children, families, and other professionals but some gaps between the program’s intentions and reality emerged. We explore the reasons for the program’s success and the implications for its further development.